Formulasi Sediaan Krim Ekstrak Etanol Lobak Tengger (Raphanus Raphanistrum L.) Dan Uji Aktivitas Antijamur Terhadap Candida Albicans ATCC 10231 - Aziz, Yaya Sulthon; Novitasari, Heni; Wulandari, Septiana Indah Ayu (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
The seaweed plant (Rhapanus raphanistrum L) has been used as a traditional medicine due to its many pharmacological effects. The tree is known to have benefits for treating fever, typhoid, syphilis, and diarrhea due to its important contents, including saponins, flavonoids, and polyphenols. The aim of this study is to standardize the extracts and make a cream preparation with a type M/A ethanol extract of the Tengger Shell (Rhapanus raphanistrum L), which can stop the development of the fungus Candida albicans. Laboratory experiments are this kind of research. The sample was taken by random sampling to test the resistance to Candida Albicans ATCC 10231. The results of this study showed that the ethanol extract of Tengger Rye (Rhapanus raphanistrum L) was obtained from the dried tengger rye bulbs using a method of maseration with 96% ethanol. The extract is thick, brownish, characteristic smell, and bitter taste, and has chemical content like flavonoids, saponins, and tannins. The resulting randomness was 13.57%. Non-specific parameters resulting from a drying suspension of 2.03%, extract type weight of 0.27%, water content of 3.26%, total ash of 14.28%, and acid insoluble ash of 2.67% meet the established quality standards. Antifungal activity suggests that the preparation of the cream ethanol extract of Tengger (Raphanus raphanistrum L.) has the ability to inhibit the fungus Candida albicans. The average diameter of formula I is 5 mm, formula II is 5mm, formula III is 10mm, and formula IV has a maximum barrier zone of 11mm. The results of research and data analysis showed that the cream ethanol extract of Tengger Shrimp (Raphanus raphanistrum L.) inhibits the fungus Candida albicans.